1998
DOI: 10.1044/jslhr.4101.188
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Poor Language Achievement Among Twins

Abstract: In order to examine the basis of familial associations with poor language achievement, 62 twinship pairs and 3 sets of triplets were studied in which at least one member presented poor oral language status in the absence of other developmental or sensory impairments. Rates of concordance for poor language were compared between the monozygotic (MZ) and dizygotic (DZ) pairs. Concordance for the MZ pairs was .96, whereas it was .69 for the DZ pairs. The DeFries-Fulker method for computing heritability of extreme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(122 citation statements)
references
References 34 publications
3
112
1
6
Order By: Relevance
“…The final study (Bishop & Hayiou-Thomas, 2007) focuses specifically on a group of children who were identified as having specific language impairment. This work was motivated by a striking anomaly in the literature looking at genetic influences on SLI: while four out of five twin studies reported very strong genetic effects DeThorne et al, 2006;Lewis & Thompson, 1992;Tomblin & Buckwalter, 1998), one study -based on the 4½-year TEDS sample -found negligible heritability for SLI (Hayiou-Thomas, Oliver & Plomin, 2005). On re-examining the data, we found that the reason for this large discrepancy had to do with ascertainment.…”
Section: Speech or Language: The Heritable Phenotype In Sli?mentioning
confidence: 90%
“…The final study (Bishop & Hayiou-Thomas, 2007) focuses specifically on a group of children who were identified as having specific language impairment. This work was motivated by a striking anomaly in the literature looking at genetic influences on SLI: while four out of five twin studies reported very strong genetic effects DeThorne et al, 2006;Lewis & Thompson, 1992;Tomblin & Buckwalter, 1998), one study -based on the 4½-year TEDS sample -found negligible heritability for SLI (Hayiou-Thomas, Oliver & Plomin, 2005). On re-examining the data, we found that the reason for this large discrepancy had to do with ascertainment.…”
Section: Speech or Language: The Heritable Phenotype In Sli?mentioning
confidence: 90%
“…Findings from twin, adoption, and genetic linkage studies provide further support for shared genetic influences on SSD, LI, and reading disorders (Bishop, North, & Donlan, 1995;Felsenfeld & Plomin, 1997;Lewis & Thompson, 1992;Stein et al, 2004;Tomblin & Buckwalter, 1998). In a recent study, Stein et al (2004) examined a region on chromosome 3 that was previously associated with RD.…”
Section: Genetic Support For the Subtyping Of Ssdmentioning
confidence: 93%
“…Findings from these studies indicate that 23-40% of firstdegree family members of individuals with speech-sound/language disorders are affected. Findings from twin and adoption studies also suggest a genetic component to speech and language (Bishop, North, & Donlan, 1995;Felsenfeld & Plomin, 1997;Lewis & Thompson, 1992;Tomblin & Buckwalter, 1998).…”
Section: Limitations Of Previous Studiesmentioning
confidence: 99%